Trichobilharzia mergi sp. nov. (Trematoda: Digenea: Schistosomatidae), a visceral schistosome of Mergus serrator (L.) (Aves: Anatidae) - Kolářová, Libuše; Skírnisson, Karl; Ferté, Hubert; Jouet, Damien (Parasitology international, 2013)
Parasitological investigations on red-breasted mergansers (Mergus serrator L.) in Iceland revealed digenean flukes of the family Schistosomatidae. Adult worms were detected in blood vessels of the large intestine and eggs were deposited in the mucosa and surrounded by granulomatous reactions. Traditional morphological methods showed that the flukes have very slender filiform bodies, males are equipped with a short gynaecophoric canal and both suckers and spatulate ends are present on each sex. Among characteristics of the flukes which render them morphologically distinct from other Trichobilharzia species are: i) males-well developed vesicula seminalis (v.s.) consisting of a short v.s. externa and a significantly longer (approx. 3 times) v.s. interna, unusually well developed genital papilla and localization of the first testis a relatively long distance posterior to the gynaecophoric canal; ii) eggs-small and elongated with slightly rounded poles and a short terminal spine. DNA taxonomic techniques confirmed that a new species had been identified, Trichobilharzia mergi sp. n. The sequence data were deposited in GenBank under the accession numbers JX456151 to JX456172. Comparison of the results with our previously published data on characterization of DNA of cercariae isolated from freshwater lymnaeid snails showed that larval development of T. mergi is associated with Radix balthica L. (=Radix peregra Müller, 1774;=Radix ovata Draparnaud, 1805).
Keywords: sekvence nukleotidů; DNA, Ribosomal; Phylogeny; střeva; Sequence Analysis, DNA; Molecular Sequence Data; Intestines; molekulární sekvence - údaje; nemoci ptáků; Island; Female; Trematode Infections; infekce červy třídy Trematoda; zvířata; Schistosomatidae; sekvenční analýza DNA; Anseriformes; ženské pohlaví; Base Sequence; Male; fylogeneze; Iceland; ribozomální DNA; Animals; Bird Diseases; mužské pohlaví